Occupational Disruption during the COVID-19 Pandemic: The Lived Experience of Community-Dwelling Older Adults. Issue 4 (11th December 2021) - Rotenberg, Shlomit; Oreper, Julie S.; Bar, Yael; Davids-Brumer, Naomi; Arbel, Ifah; Dawson, Deirdre R.
Abstract: This qualitative descriptive study presents the experience of an abrupt disruption of daily activities among community-dwelling older adults during the early months of the COVID-19 pandemic. Sixteen older adults (age: 71 ± 6.4) were interviewed in April–June, 2020. Five themes were identified: (1) Understanding and applying COVID-19 guidelines: guidelines were clear and participants adhered closely to them, motivated mainly by fear; ageing-specific guidelines are needed. (2) Daily life during lockdown: the abrupt occupational disruption was managed by transitioning to virtual activities, and/or performing more activities at home. New daily activities were generally more sedentary and less meaningful. (3) Social context: family assistance aroused mixed feelings, as it compromised independence; limited compliance at the community level created stress. (4) Mood and affect: mood often fluctuated, and participants employed various coping strategies. (5) Aging: participants became more aware of their age and were concerned about negative health implications of adherence to COVID-19 guidelines.